Evaluation of heavy metals and environmental risk assessment in the Mangrove Forest of Kuala Selangor estuary, Malaysia - ELTurk, Mohammed; Abdullah, Rosazlin; Rozainah, Mohamad Zakaria; Bakar, Nor Kartini Abu (Elsevier, 2018)
This study was carried out to evaluate the distribution, enrichment and ecological risk of heavy metals (arsenic (As), zinc (Zn), manganese (Mn), copper (Cu) and lead (Pb)) concentration in Kuala Selangor estuary at the Kuala Selangor Nature Park. The results suggested that As and Pb in sediment were as high as the background value, suggesting the presence of anthropogenic contamination. The risk assessment of sediment Igeo, CD, and PERI, on the other hand, showed low risk of heavy metals in Kuala Selangor estuary. Meanwhile, risk assessment code (RAC) results showed that Mn, As and Zn presented medium to high level of environmental risk. The translocation factor and bioaccumulation factors of heavy metal concentration by mangrove vegetation showed a variety of trends, which indicates the different partitioning and uptake ability of heavy metal in the tissues of different mangrove species. Therefore, underscores the importance of preserving the high diversity of mangroves at securing the health and productivity of the coastal region. These results may play a critical role in facilitating decision makers in managing the sustainability of mangrove forests.